The International Framework for Cyber-Attacks Under the Rules of International Humanitarian Law - Al-Billeh, Tareq; Al-Mudanat, Jessica; Almamari, Abdulaziz; Khashashneh, Tawfiq; Al-Hailat , Odai (Lembaga Contrarius Indonesia, 2025)
The research paper analyses the extent of enforcement of the rules of international humanitarian law on perpetrators of cyber-attacks by stating the nature of cyber-attacks and identifying the types of cyber-attacks, highlighting international efforts to regulate cyber-attacks under international humanitarian law, deducing the extent of the suitability of the rules of international humanitarian law that govern cyber-attacks, and determining the extent of the jurisdiction of the International Criminal Court to punish perpetrators of cyber-attacks. This study followed the analytical and critical approach by reviewing the rules of international humanitarian law and the extent of their applicability to cyber-attacks. Finally, the study came to a conclusion with a list of results and suggestions. The most important of these is that the way international justice is done needs to change completely so that the International Criminal Court can better handle cybercrimes. This is to ensure that the inclusion of cybercrimes under the jurisdiction of the International Criminal Court aligns with the principles of international humanitarian law, while also highlighting the similarities between cyber weapons and conventional weapons. This is achieved through collaboration between legal and technical experts in addressing the intricacies of cybercrimes, promoting accountability, and bolstering justice in the digital era